Hubungan Indeks Massa Tubuh Dengan Gangguan Otot - Setiadi Setiadi; Dedi Irawandi (Yayasan Jompa Research and Development, 2023)
Musculoskeletal disorders occur as a result of student activity, psychosocial, and environmental factors. Another factor that can cause musculoskeletal disorders is body mass index (BMI), due to the influence of anthropometric measurements related to the balance of the skeletal structure in receiving bodyweight loads and work The purpose of this study was to determine the relationship between body mass index and musculoskeletal disorders in Hang Tuah STIKES Surabaya students. The research design uses observational analytic with a cross sectional approach. The results of the study of the majority of students, namely as many as 65% of students have a normal BMI. 85.7% of students fall into the category of no musculoskeletal disorders. The implication of this study is that a higher or lower body mass index can affect the occurrence of musculoskeletal disorders. Students need to balance the ideal BMI by implementing a clean and healthy lifestyle so as not to cause musculoskeletal disorders.